2016
DOI: 10.1002/asia.201601144
|View full text |Cite
|
Sign up to set email alerts
|

Energetic 4,4′‐Oxybis[3,3′‐(1‐hydroxytetrazolyl)]furazan and Its Salts

Abstract: Energetic compounds that incorporate multiple nitrogen-rich heterocycles are of great interest for high-density energetic materials. A facile synthetic strategy to combine an oxy bridge and furazan groups, as well as tetrazole-ols, into a molecule (5) was found. Some energetic salts based on 5 were prepared by neutralization. All of the compounds were fully characterized. Additionally, the structure of 7 has been elucidated by single-crystal XRD analysis. Physicochemical and energetic properties were also stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…As shown in Figure , the signals of 15 N NMR for anions in salts 2 ‐ 5 were located at around ‐7.3∼‐66.0 (N1‐N4 in hydroxytetrazole ring), ‐13.5 (N7 in nitro group) and 33.2‐42.6 (N5‐N6 in furazan ring) ppm, which were almost identical in all the anions. The signals appeared at ‐297.2, ‐357.2, and ‐304.1 ppm, which were corresponding to the hydroxylammonium, ammonium and guanidinium, respecitively, and were in accordance with similar structures in reported literatures …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…As shown in Figure , the signals of 15 N NMR for anions in salts 2 ‐ 5 were located at around ‐7.3∼‐66.0 (N1‐N4 in hydroxytetrazole ring), ‐13.5 (N7 in nitro group) and 33.2‐42.6 (N5‐N6 in furazan ring) ppm, which were almost identical in all the anions. The signals appeared at ‐297.2, ‐357.2, and ‐304.1 ppm, which were corresponding to the hydroxylammonium, ammonium and guanidinium, respecitively, and were in accordance with similar structures in reported literatures …”
Section: Resultssupporting
confidence: 89%
“…On the other hand, in order to improve the energetic properties of tetrazoles, several recently published studies showed that introduction of N‐oxides yields compounds with even higher densities and stabilities, lower sensitivities and better oxygen balances ,. Up to now, although several typical energetic salts, such as 3‐nitroamino‐4‐(tetrazol‐1‐olate) furazanate and 4,4’‐Oxybis[3,3’‐(1‐hydroxytetrazolyl)]furazanate, have been reported and shown in Figure ,, they can hardly achieve an good balance between high energy and low sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Among nitrogen-rich five-membered heterocycles, triazole and tetrazole rings have high HOF, good stability, and conjugated structures. [22][23][24] Introduction of hydroxyl groups into the tetrazole ring further increases its HOF and oxygen balance 14,[25][26][27][28] and provides hydrogen bond donors. The deprotonation of the hydroxyl moiety also opens up the possibility for further modifications on the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Despite tetrazoles having multiple applications in many fields, hydroxytetrazoles have received limited attention outside of the energetics community. Therefore, the simplest strategy involves the acid-catalyzed cyclization of azidoximes , forming the 1-hydroxytetrazole isomer.…”
Section: Introductionmentioning
confidence: 99%